THE OPENNESS OF MARRIED COUPLE TO LIFE: MODERN MEDICAL AND TECHNOLOGICAL POSSIBILITIES AND CHALLENGES — A THEOLOGICAL RESPONSE - Davis, J. Charles (Asian Horizons, 2014)
This article addresses the issue of the fundamental openness of the married couple to procreation of new life and the methods through which the number of children in a family can be rightfully limited. Procreation and responsible parenthood are key themes in the first part. In the second part, the article discusses the medical technological possibilities and challenges in matters of fertility and infertility and offers an ethical response in the light of the teachings of the Catholic Church. Medical treatments that assist procreative act are morally acceptable and technological treatments that substitute for conjugal act are morally unacceptable. The article thus tries to distinguish the technologies and researches that promote and enhance human life from those that dehumanize making it a product or commodity.